Medicines as a Service A New Commercial Model for Big Pharma in the Postblockbuster World - Mattke, Soeren (RAND Corporation, 2012)
The pharmaceutical industry can reconfigure its considerable resources to develop innovative and meaningful business models that are based on services that improve access and adherence to prescription drugs for common chronic conditions. Such innovation beyond drug development is consistent with the core capabilities of large pharmaceutical companies and has the potential to achieve profit levels similar to those of its traditional models.